Feminism: An Alternative Approach to International Relations - Kumar, Ajay (Technium Social Sciences Journal, 2023)
Almost half of the world’s population is women, so how can it be possible that any discipline is one-sided or only male-oriented? Similarly, all meta-theories cannot impose rules and regulations on the whole world as international relations theories just by being malevolent. In this case, the only alternative is to foster feminist theory, not ignore them as often occurs in IR theories, which implies demeaning them through various conceptions. This can be considered a one-sided perspective or approach to understand the world, which divides men and women into supremacists and subordinates respectively. Feminist IR, therefore, stands as an alternative approach to understanding the masculine IR that questions it as well as provides ‘reflective theories’ from literature to psychology to history, and has been seeking a safe place in IR for the last four decades as a serious academic discipline. This article will try to examine the feminist theories of the IR discipline as an alternative approach, for which descriptive and analytical method was adopted for this explanatory research. As a result, it has been found that feminist IR has searched out the gap between IR theories and it has been given a new shape to IR discipline in the form of a critical feminist IR theory as an alternate.